How the whale became and other stories - Hughes, Ted, 1930-; Adamson, George (London : Faber and Faber, 1963)
A collection of creation stories explaining why owls hunt at night, why the dog was chosen to guard farm animals, why polar bears live at the North Pole, and how the elephant came to accept its unique and wonderful qualities.
"First published in Great Britain in 1963 by Faber and Faber Limited"--T.p. verso.
4.6
3-6
Keywords: Children's stories, English; Creation -- Juvenile fiction; Animals -- Fiction; Creation -- Fiction; Short stories; Animals -- Fiction; Creation -- Fiction; Short stories